2013
DOI: 10.4276/030802213x13627524435108
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Approved Mental Health Professional Role and Occupational Therapy

Abstract: Act 2007 was to broaden the professional groups eligible to undertake specific roles under the Act. One such role was the approved mental health professional (AMHP), whose responsibility is to conduct assessments of people deemed mentally disordered to determine whether they meet the criteria for detention, known as 'sectioning'. Traditionally, this role was undertaken by social workers. Although occupational therapists are now eligible to undertake the role, uptake has been low. Method: A critical literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, the structured nature of the skills training did not appear to suit everyone. The intervention was more successful when based on participants’ goals rather than workers’ preferences, which enabled them to be more engaged in decisions involving their own care and motivated towards recovery [35]. …”
Section: Resultsmentioning
confidence: 99%
“…However, the structured nature of the skills training did not appear to suit everyone. The intervention was more successful when based on participants’ goals rather than workers’ preferences, which enabled them to be more engaged in decisions involving their own care and motivated towards recovery [35]. …”
Section: Resultsmentioning
confidence: 99%
“…The literature is relatively thin on any explanation as to why so few nurses have taken up the AMHP role. Perceived tensions about a damage to therapeutic relationship with individual clients have been raised if nurses, occupational therapists and psychologists undertake AMHP duties (Holmes, 2002; Knott and Bannigan, 2013; Coffey and Hannigan, 2013; Hurley and Linsley, 2006). However, there are some evidence from both social work (Coffey and Hannigan, 2013) and nursing (Coffey and Hannigan, 2013; Ashmore, 2010) that it is possible to maintain a therapeutic relationship and execute a statutory role, even though it can be challenging (Bowers et al , 2003; Hurley and Linsley, 2006).…”
Section: Nursing and The Emergence Of The Amhp Rolementioning
confidence: 99%
“…However, there are some evidence from both social work (Coffey and Hannigan, 2013) and nursing (Coffey and Hannigan, 2013; Ashmore, 2010) that it is possible to maintain a therapeutic relationship and execute a statutory role, even though it can be challenging (Bowers et al , 2003; Hurley and Linsley, 2006). Finally, the requirement in some instances eligible professionals to first undertake a specific academic mental health module as preparation for starting the AMHP training has been identified as a possible barrier, or disincentive, to non-social workers (Knott and Bannigan, 2013). This may be because the requirement to complete this module is seen as part of the continuing professional development (CPD) for social workers, and therefore the requirement to undertake this module does not translate well to CPD education pathways for allied health professionals.…”
Section: Nursing and The Emergence Of The Amhp Rolementioning
confidence: 99%
“…The later comparative study by Bressington, Wells, and Graham (2011) found that although professionals from differing backgrounds enter AMHP training with varying mental health knowledge, the impact of the course by the time of completion leaves a high level of harmonisation between professions including a shared understanding of the AMHP role and the social perspective in mental health (see also Bowers, Clark, and Callaghan 2003;Coffey and Hannigan 2013;Holmes 2002;Knott and Bannigan 2013). The studies by Peay (2003) and Bressington, Wells, and Graham (2011) underline that differences between AMHPs are less likely to be notable than is often claimed and indicate that further research is required.…”
Section: Previous Studiesmentioning
confidence: 99%